A CRITICAL REVIEW OF THE METAPHYSICAL DIVERGENCES AMONG COMMENTATORS IN URDU TAFSIRS - Abdul Satar; Dr. Farhat Naseem Alvi (Journal of Religion and Society, 2024)
The meaning of Mu‘jizah (miracle) is to render someone helpless, to compel, to astonish the intellect, or for an event to occur in such a way that no scientific explanation can be understood—something happening without apparent causes. In other words, an act that breaks the natural order is called a Mu‘jizah (miracle). Certain extraordinary events, which go against the usual patterns of nature, are manifested by Allah through the hands of His messengers and prophets, in such a way that people are left unable to replicate them. These events serve to demonstrate the truth of the prophet's claim to prophethood. The unusual events shown by prophets and messengers are called miracles (Mu‘jizat).A miracle is also a proof of a prophet’s truthfulness. When a prophet openly claims his prophethood and takes responsibility for presenting things that are naturally impossible, he invites the deniers to produce something similar. Then Allah causes such extraordinary events to occur according to the prophet’s claim, and the deniers remain helpless. This is what is called a miracle. For example, the she-camel of Prophet Ṣāliḥ (peace be upon him), the staff of Prophet Mūsā (Moses) turning into a snake, or Prophet ʿĪsā (Jesus) bringing the dead back to life, curing those born blind and the lepers. Similarly, the Prophet Muhammad ﷺ was granted many miracles. When the disbelievers of Quraysh demanded a miracle from the Prophet Muhammad ﷺ and said, “If you are truly a prophet, then split the moon in two,” the Prophet ﷺ pointed towards the moon, and it split into two parts.Therefore, the scholarly researchers (‘ulama muḥaqqiqīn) have critiqued these individuals, refuting them with evidence from the Qur'an, Sunnah, the understanding of the pious predecessors (salaf), and the hadith scholars. Keywords: Mu‘jizah, miracle, Prophet, pious predecessors.